Antimicrobial Assessment of Resins from Calophyllum Antillanum and Calophyllum Inophyllum. (30th October 2015) - Cuesta‐Rubio, Osmany; Oubada, Ahmad; Bello, Adonis; Maes, Louis; Cos, Paul; Monzote, Lianet
Abstract : The Calophyllum genus is well‐known for its antimicrobial and cytotoxic activities, and therefore, we analyzed these biological activities for resins of Calophyllum antillanum and Calophyllum inophyllum growing in Cuba. C .  antillanum resins showed a potent activity against Plasmodium falciparum (IC50  = 0.3 ± 0.1 µg/mL), while its cytotoxicity against MRC‐5 cells was much lower (IC50  = 21.6 ± 1.1 µg/mL). In contrary, the resin of C .  inophyllum showed an unspecific activity. The presence of apetalic acid, isoapetalic acid, calolongic acid, pinetoric acid I, pinetoric acid II, isocalolongic acid, pinetoric acid III, and isopinetoric acid III in C .  antillanum resins was also confirmed. These results demonstrated for the first time the potential activity of C .  antillanum resins against P .  falciparum . Copyright © 2015 John Wiley & Sons, Ltd.